Did emergency liquidity assistance (ELA) of the ECB delay the bankruptcy of Greek banks? - Martin R. Götz; Rainer Haselmann; Jan Pieter Krahnen; Sascha Steffen (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The European Central Bank (ECB) increased the emergency liquidity assistance (ELA) for Greek banks from exteuro50 billion in February 2015 to approximately exteuro90 billion in June 2015. Its actions were accompanied by a discussion among academics, politicians and practitioners regarding the legitimacy of the ELA. Some have even accused the ECB of deliberately delaying the bankruptcy filing of already insolvent Greek banks. We take the claim regarding insolvency delay as an opportunity to highlight the underlying economics of the ELA program and discuss its legitimacy in the current situation. We start by characterizing the complex interrelationship of the European Union, the ECB and the Greek banks through the lens of financial economics, with a particular focus on the political economy of a monetary union with incomplete fiscal union (or fiscal consolidation). Combining these two issues, we examine the decision of the ECB to continue the provision of ELA to Greek banks. Our conclusions, drawn from the analysis, do not support the claim that the ECB's actions are consistent with a delayed filing for insolvency.
Keywords: 330; emergency liquidity assistance (ELA); economic and monetary union; banking supervision; Greece